Examining the antecedents of impulse purchase among facebook commerce (f-commerce) users / Leong Lai Ying - Leong, Lai Ying (2017)
Nowadays, Facebook commerce or f-commerce has become a new paradigm in e-commerce. Even though there is a huge business potential in f-commerce, the purchase behaviour in f-commerce is still not well-studied with only a few studies are related to impulse buying through f-commerce and yet the studies are not from a holistic and integrated point of view. The theoretical framework development of this study is based on Social Impact Theory, Theory of Web Usage and Trust Transference Theory. This study investigated the antecedents of trust motivation; the predictors of participation, browsing, f-commerce usage intensity; and their influence on urge to impulsively purchase and impulse purchase from the context of f-commerce. The effect of urgency towards urge to impulsively purchase and impulse purchase were also determined. All items in the questionnaire were adapted from past studies and have been rigorously tested during the pre-test and pilot test. Based on purposive sampling technique, 1000 f-commerce users from Klang Valley who have spending power was selected and their responses were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM). The model can explain 46.4%, 31.6%, 52.6%, 47.1%, 33.4% and 42.1% variance in browsing, f-commerce usage intensity, impulse purchase, participation, trust motivation and urge to impulsively purchase respectively. The result also showed that urge to impulsively purchase partially mediates the relationship between urgency and impulse purchase. These findings will be beneficial to the online retailers, marketers and other f-commerce stakeholders in terms of formulating their marketing strategies and policies as well as providing novel insight in understanding impulsive behaviour in f-commerce.